(untitled) (Anclajes, 2022)
While current experiences around time seem dominated by speed, immediate obsolescence and the short-termism, the works that make up this dossier bring together heterogeneous aesthetic materials in a cultural series that outlines alternative ways of processing, inhabiting, reimagining temporality. Through the proposed analysis, literary, cinematographic and theatrical works of contemporary Argentina enter into a dialogue based on a common commitment to the long term, to long duration as a unit of measurement for their narrative projects. Thus, time recovers the lost centrality in narrative imaginations –and critical reflections–, but it does so in the form of questioning its perception, the discontinuity of its rhythms and chronologies, the interrogation of what it means to inhabit time and the opening to the different temporalities that are coupled, descompose or ignored behind this use of the singular.